RE-CLASSIFICATION OF THE NEGLECTED VARIABLE V480 AQL - Virnina, N. A.; Maslova, N.; Krajci, T. (Одеські астрономічні публікації, 2014)
We present the results of multicoloured photometric study of previously neglected variable star V480 Aql. Our V RI observations prove that this star belongs to classical Cepheids with the period of P = 19d.0016. We also propose an empirical dependence between colour indices and temperature of supergiants, which, according to the nature of Cepheids, enabled us to determine minimum and maximum temperatures of V480 Aql.